A hybrid P2P approach to service discovery in the cloud - Zhou, J.; Abdullah, N.A.; Shi, Z. (2011)
Highly scalable techniques for service discovery are key to the efficient use of Cloud resources, since the Cloud computing appears to be part of the mainstream computing in a few years. We embarked on a preliminary study on Cloud service discovery by adopting an unstructured P2P paradigm. We developed an efficient mechanism for routing of service requests by coupling a number of components: one-hop replication, semanticaware message routing, topology reorganization, and supernodes. A number of experiments were carried out that demonstrated the expected performance of the proposed P2P search scheme.